Combination of BRCA deep targeted sequencing and shallow whole genome sequencing to detect homologous recombination deficiency in ovarian cancer - Nguyen Hoang, Thien-Phuc; Tran, Nam H. B.; Nguyen, Tien Anh; Ngo, My T. T.; Doan, Anh Duong; Nguyen, Du Quyen; Tang, Hung Sang; Nguyen, Duy Sinh; Thi, Cam Tu Nguyen; Thi, Thanh Thuy Do; Nguyen, Hoai-Nghia; Giang, Hoa; et al. (Frontiers in Oncology, 2025)
BackgroundsAssessing homologous recombination deficiency (HRD) has been recommended by clinical guidelines for patients with ovarian cancer (OC) as it predicts sensitivity to poly (ADP-ribose) polymerase inhibitors (PARPi). However, HRD testing is complex and either inaccessible or unaffordable for majority of OC patients in developing countries. Consequently, the prevalence of HRD in OC remains unknown.MethodsWe examined HRD status of 77 Vietnamese patients with OC using a new laboratory-developed test (HRD Insight, Gene Solutions). Tumor DNA was extracted from FFPE samples, followed by next-generation sequencing to detect deleterious or suspected deleterious variants in BRCA1/2 genes. Shallow whole genome sequencing was performed to determine the whole Genomic Instability (wGI) score by assessing the presence of large-scale intra-chromosomal copy number alterations.ResultsThe assay was first benchmarked against commercial HRD kits including TruSight Oncology 500 HRD (Illumina), SOPHiA DDM HRD Solutions (Sophia Genetics) and HRD Focus Panel (AmoyDx), and showed an overall percent agreement of 90.0%, 96.3%, and 96.4% respectively. The successful rate of sequencing was 94.8% (73/77) and the prevalence of HRD in OC patients was 54.8% (40/73). BRCA mutations and positive wGI scores were found in 16.4% (12/73) and 47.9% (35/73) of the patients respectively. Among those with wild-type BRCA1/2, 40.5% of them had positive wGI scores and hence positive HRD. Age at diagnosis was not affected by both BRCA and wGI status.ConclusionsHRD Insight assay could accurately and robustly determine the HRD status of ovarian tissue samples, including those with low quality.